School Choice and Equity Current Policies in OECD Countries and a Literature Review - Musset, Pauline (OECD Education Working Papers, 2012)
This report discusses the most relevant issues concerning school choice schemes, and how they intertwine with equity considerations, through a literature review and analysis of the effects different types of school choice programmes have on equity. In the last 25 years, more than two-thirds of OECD countries have increased school choice opportunities for parents. The empirical evidence reviewed here reveals that providing full parental school choice results in further student segregation between schools, by ability, socio-economic and ethnic background, and in greater inequities across education systems. The report identifies certain characteristics of programmes that can prevent schools from hand-picking their students - crowding out disadvantaged and low performing students. As school choice is here to stay, countries should explore choice designs that balance parents' freedom to choose with equity considerations: this report develops two particular schemes: controlled choice programmes - also called flexible enrolment schemes - and weighted funding formula